Ag-Cu modified ZSM-5 zeolite to effectively eliminate NOx and slip ammonia from coal-fired flue gas: Catalytic performance and characterization. Issue 5 (October 2022) - Liu, Wenjie; Long, Yifei; Zhang, Jingbo; Liu, Shinian; Zhou, Yongyan; Tong, Xin; Yin, Yajie; Li, Xiaoyi; Hu, Kang; Hu, Jiangjun
Abstract: To eliminate NOx emission and slip ammonia from coal-fired plants, ZSM-5 zeolites were modified with copper and different amount of silver. According to the activity measurement results, Ag1.5 -Cu/ZSM-5 zeolite could exhibit 100 % NH3 conversion efficiency at 350 ℃ and the N2 selectivity was more than 90 %. Meanwhile, when NO was introduced in the gas flow, the NO and NH3 conversion efficiency of Ag1.5 -Cu/ZSM-5 reached 97 % and 100 % at 300 ℃. The catalyst also showed good tolerance to H2 O and SO2 . XRD, BET, SEM and TEM experiments confirmed that the addition of silver and copper oxides would not destroy the MFI skeleton structure or significantly destroy the microporous and mesoporous structure of the molecular sieve. Moreover, Ag-Cu/ZSM-5 catalyst exhibited stronger surface acidity and promoted the NH3 adsorption ability (NH3 -TPD). In addition, there were more active oxygen on Ag-Cu/ZSM-5 catalyst resulting from the interaction between silver and copper oxides, which contributed to its better redox performance (XPS and H2 -TPR). Graphical Abstract: ga1 Highlights: ZSM-5 zeolites modified with Cu and different amount of Ag were prepared by impregnation method. Ag modification significantly improved the removal efficiency of slip NH3 and NO. Ag1.5 /Cu-ZSM5 catalyst showed good tolerance to SO2 and H2 O. Ag modification could increase the surface active oxygen, acidic sites and redox property of ZSM-5 zeolites due to the interaction between Ag and Cu oxides.